Online information seeking behavior among academicians: a case study of UiTM Melaka / Mazlan Salleh, Fazlul Haque Kamarudin and Rohana Ramli - Salleh, Mazlan; Kamarudin, Fazlul Haque; Ramli, Rohana (2011)
This research aims to investigate factors that influence online information seeking, types of information resources frequently used, online databases usage among academicians specifically in UiTM Melaka, and the suitability of online databases provided by UiTM Resource Centre. Data were collected by using questionnaires distributed to 205 academicians. Results show that the factors include the skill of using and accessibility of the online information, and academic rank, qualification and teaching experience of academicians. Furthermore, doing and completing research work are the main purposes of online information seeking. Academicians preferred to communicate with each other and consult with knowledgeable person, and abstract journals and review articles are types of resources used. Approximately 114 academicians (81.2%) used online databases and 62 of them frequently used it. Proquest and Emerald are the two most popular providers. About 100 academicians (74.3%) used UiTM Digital Library, 82.7% used it to access subscribed online databases and 81.7% accessed collections of past-year's final examination questions paper. Most academicians (80.8%) were satisfied with the online resources provided and 84.6% agreed that online databases provided are suitable and sufficient enough for them. The majority of academicians faced a common problem while seeking online information, which is the medium speed of network access in campus.